Menggugah Kesadaran Pariwisata Pelajar SMU/SMK di Kabupaten Belitung melalui Kegiatan Tourism Goes to School - Rina Fitriana; Duta Fitriana Siregar (Pusat Studi Sosial dan Pengabdian Masyarakat Fisipkum Universitas Serang Raya, 2020)
This article talks about an activity called Tourism Goes to School, a training of tourism consciousness and seven enchantments designed for High School Students. It is held in Students Hall of SMUN 1 Tanjung Pandan, Belitung. The purpose of this activity is to raise tourism consciousness and to socialize seven enchantments to the high school students in order to prepare them in dealing and interacting with the tourists. Along with the number of tourist visits that keeps increasing since few years ago, precisely since the boom of the movie titled Laskar Pelangi, the government of Belitung has developed its tourism sector, including by opening some new tourism objects and renovating existed attractions to fulfill the expectation of tourists. The method used in this community service is socialization, tutorial, discussion, and evaluation. The participant involved in the training was 100 students from grades 10 and 11 who came from several high schools around Tanjung Pandan, Belitung. The result of this training is that the participants understand what tourism consciousness and seven enchantment are, as well as how important the concepts in tourism and how to apply both into everyday life. Keyword: Human Resource in Tourism, Tourism Consciousness and Seven Enchantments, Tourism Goes to School, Belitung